Zróżnicowanie produkcji mleka w Polsce i jego uwarunkowania - Majewski, Janusz (Factors Determining Regional Differentiation of Milk Production in Poland, 2006)
The paper presents regional differentiation in the level of milk production per hectare of agricultural land area and main factors which influenced these differences. The regression analysis and cluster analysis show those factors. They were average annual quantity of milk per cow, share of meadows and pastures in agricultural land area, yields of meadow hay per hectare, quality of agricultural land area, share of agricultural land in grand total area and share of milk production from private farms in total milk production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 66-71